(3aQGFO GdYbhO GdYdhjI dMd CdaGX TQM GdCRgQjIs - (3Ydj Hf EHQGgje GdMdHjs; (3GdTjN NGdO GdGRgQj , Rjf GdOjf NGdO Hf YHO Gddg Hf CHj HcQ Hf eMeO GdGRgQj, GdhbGO,J (B905 (3g` s
(3ChdgG (B:s
(3MeOkG def QaY ef GfJUH dNOeI Gdafhf GdYQHjI CeG HYO ajbhd GdabjQ deG QCjJ TQM GdCRgQjI ChdY Hg GdeMUdhf ddahGFO GdfMhjI s
(3BNQgG (B:s
(3hCLjH HCf GdfGS jhShShf CjVkG ai UOhQ GdfGS HeYfi jdjb Hge ai GdXGgQ Ke JUd hShSJge Edi GdbdH hGdMeO ddg GdPi gOGfG dgPG s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B297 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B96s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs